In vivo reflectance confocal microscopy terminology in theTurkish language - Fezal Özdemir; Mehmet Salih Gürel; Işıl Karaarslan; Vefa Aslı Turgut Erdemir; Ayşe Esra Koku Aksu; Ayda Acar (Galenos Publishing House, 2021)
In vivo reflectance confocal microscopy (RCM) is a diagnostic method to examine a skin lesion at the cellular level in vivo without biopsy. It provides non-invasive, high resolution imaging for diagnosis and follow-up of malignant, benign skin tumors and inflammatory dermatologic diseases, and its use is spreading worldwide. Standard terminology which has been used in RCM was described earlier in the English language. This study aimed to propose a Turkish terminology for RCM to allow Turkish-speaking dermatologists to communicate in a homogeneous language and familiarize themselves with the terminology of this new diagnostic technic. Six Turkish-speaking dermatologists with RCM experience participated in the study. RCM terminology used in English was determined and translated into Turkish. Turkish terms and their definitions were reviewed by each participant and the consensus was provided in the group. Finally, philology department examined the last version of the terms and the study was finalized. The terms, definitions and the translations of the terms have been identified, and the Turkish RCM terminology has been created and shown. Turkish RCM terminology will provide Turkish-speaking dermatologists to describe their findings in a homogenous language.